Voices Unheard: Navigating Language Challenges Among Pharmacy Students in Pakistan - Meo, Hafsa Karamat; Afzaal, Aymen; Aleem, Faiza (University of Chitral Journal of Linguistics and Literature, 2024)
The English language holds a crucial role in the Pakistani education system, yet many Pakistani students encounter difficulties when it comes to speaking English in their classrooms. Therefore, there was a need to investigate the challenges these students face while attempting to speak English. This research draws upon a combination of Lev Vygotsky's social constructivism and constructivist theoretical frameworks to delve into the constructivist aspects that uncover the social realities and influences compelling students in Pakistan to switch to their local language, Urdu, instead of using English. Social constructivism emphasizes the role of culture and social context in the learning process, making it a suitable lens for this study. The study aims to achieve two main objectives: first, to identify the problem students encounter when using English in classrooms, and second, to gain insights into the perspectives of non-native English-speaking students. To achieve these goals, a quantitative research method was employed, utilizing an open-ended questionnaire designed to gather data from 100 students in the Pharmacy department at the University of Lahore. Among the participants, most have Urdu as their native language, while few were who use English as a foreign language, with varying levels of proficiency. The study's findings reveal that students generally appreciate the English learning environment as it motivates them to use English outside of their classrooms. However, they face reluctance to speak English due to social and psychological factors, including the fear of judgment and a lack of confidence. The study further demonstrates that students find it more convenient to communicate in their first language because it allows them to express their ideas more comfortably. In conclusion, this research contributes valuable insights to the broader discourse on language education, offering guidance for policymakers, educators, and researchers.